COVID-19 Death Occurrences, Pandemic Fatigue, and Well-Being. Issue 7 (3rd October 2022) - Cleofas, Jerome V.; Oducado, Ryan Michael F.
Abstract: Fifteen months since the pandemic started, the Philippines continues its struggle to control COVID-19 cases and deaths. This cross-sectional study, with 1, 467 respondents, examined the predictive role of occurrences of COVID-19 related deaths within social circles to pandemic fatigue and selected well-being outcomes. Findings suggest that personally knowing someone who died from COVID-19 significantly increases pandemic fatigue, subjective well-being, and life satisfaction.